Energy and velocity-based multipath routing protocol for VANET. (2019) - Bhagyavathi, M.; Saritha, V.
The VANET is a type of network that can be built randomly, quickly and temporarily without any standard infrastructure. In VANET, routing of data is an interesting and challenging task because of the high mobility. Therefore, the routing algorithm for VANETs is an imperative issue, particularly in vehicle to vehicle communication. This paper proposes a multipath routing algorithm for VANET named energy and velocity based multipath routing protocol (EVMRP) based on available bandwidth, residual energy and relative velocity. The most important point of the proposed algorithm is setting the CWmax as the available bandwidth of the path. The proposed algorithm is tested on the QoS parameters like end-to-end delay, throughput and packet loss. The results clearly indicate that the proposed algorithm, EVMRP outperforms when compared to the legacy systems like AOMDV.